Preparedness for Studies and their most Influencing Factors - Alondere, Linda (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
With the changes in the quality of education requirements and the study opportunities, it is essential to find out how youth’s readiness to study develops, and what are its’ contributing factors. The aim is to clarify the explanation of the definition „readiness”. Analyzing literature, it is concluded that in many respects readiness for concrete studies is dependent on the youth’s motives and motivation, major and minor needs, system of values, socially financial circumstances, individual characters, temperament, individually-psychological characteristics, physical and physiological growth, on the state’s policy in the fields of education, youth, and jurisprudence, as well as on youth's attitudes to society and themselves.